Estimation of an elite road cyclist mechanical power and energy cost wearing standard and aero helmets: an analytical procedure and numerical simulations approach - Forte, P.; Marinho, D. A.; Barbosa, T. M.; Morais, J. E. (European Journal of Human Movement, 2021)
The aim of this study was to assess and compare by numerical simulations and analytical models the resistive forces, mechanical power and energy cost using two different types of road helmets (standard vs aero road helmet). An elite cyclist was scanned on the racing bicycle, wearing his competition gear and helmets. Numerical simulations by Computational Fluid Dynamics were carried-out at 11.11 m/s (40 km/h) and 20.83 m/s (75 km/) to extract the drag force. The mechanical power and energy cost were estimated by analytical procedures. The drag force were between 9.93 N and 66.96 N across the selected speeds and helmets. The power to overcome drag were 182.19 W and 1121.40 W. The total power lower and higher values were 271.05 W and 1558.02 W. The energy cost estimation was between 106.89 J/m and 381.40 J/m across the different speeds and helmets. The standard helmet imposed higher drag and demanded more power.